Discovery of Novel HPK1 Inhibitors Through Structure-Based Virtual Screening - Ge, Huizhen; Peng, Lizeng; Sun, Zhou; Liu, Huanxiang; Shen, Yulin; Yao, Xiaojun (Frontiers in Pharmacology, 2022)
Hematopoietic progenitor kinase (HPK1), a negative regulator of T cell receptor (TCR) and B cell signaling, has been recognized as a novel anti-tumor immunotherapy target. In this study, docking-based virtual screening and kinase inhibition assay were conducted to identify novel inhibitors of HPK1. The kinase inhibition assay demonstrated that 5 compounds with IC50 values below 20μM and the most potent one (compound M074-2865) with IC50 of 2.93±0.09μM. Molecular dynamics (MD) simulation was carried out to delved into the interaction of Sunitinib and the newly identified compound M074-2865 to the HPK1 kinase domain. The 5 compounds identified in this study could be considered as promising scaffold for further development of HPK1 inhibitors for immunity therapy.